2022
DOI: 10.1186/s13293-022-00431-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between cardiovascular diseases and dementia subtypes: a prospective analysis of 464,616 UK Biobank participants

Abstract: Background Whether the association of cardiovascular diseases (CVDs) with dementia differs by sex remains unclear, and the role of socioeconomic, lifestyle, genetic, and medical factors in their association is unknown. Methods We used data from the UK Biobank, a population-based cohort study of 502,649 individuals. We used Cox proportional hazards models to estimate sex-specific hazard ratios (HRs) and 95% confidence intervals (CI), and women-to-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…Recent studies also point towards a biphasic association between BMI and dementia ( Kivimäki et al, 2018 , Pedditizi et al, 2016 ). For example, while midlife obesity predicts risk for dementia ( Albanese et al, 2017 , Floud et al, 2020 , Pedditizi et al, 2016 ), the prevalence of dementia has been found to be higher in underweight than in normal weight or overweight females ( Dong et al, 2022 ). Prodromal stages of neurodegenerative diseases can involve weight loss as a result of disrupted brain function and dietary changes ( Floud et al, 2020 , Gu et al, 2014 ), and longitudinal studies targeting early markers of neurodegeneration may further the understanding of changes in body weight, brain health, and dementia risk in females.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also point towards a biphasic association between BMI and dementia ( Kivimäki et al, 2018 , Pedditizi et al, 2016 ). For example, while midlife obesity predicts risk for dementia ( Albanese et al, 2017 , Floud et al, 2020 , Pedditizi et al, 2016 ), the prevalence of dementia has been found to be higher in underweight than in normal weight or overweight females ( Dong et al, 2022 ). Prodromal stages of neurodegenerative diseases can involve weight loss as a result of disrupted brain function and dietary changes ( Floud et al, 2020 , Gu et al, 2014 ), and longitudinal studies targeting early markers of neurodegeneration may further the understanding of changes in body weight, brain health, and dementia risk in females.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also point towards a biphasic association between BMI and dementia (Kivimäki et al, 2018;Pedditizi et al, 2016). For example, while midlife obesity predicts risk for dementia (Albanese et al, 2017;Floud et al, 2020;Pedditizi et al, 2016), the prevalence of dementia has been found to be higher in underweight than in normal weight or overweight females (Dong et al, 2022). Prodromal stages of neurodegenerative diseases can involve weight loss as a result of disrupted brain function and dietary changes (Floud et al, 2020;Gu et al, 2014), and longitudinal studies targeting early markers of neurodegeneration may further the understanding of changes in body weight, brain health, and dementia risk in females.…”
Section: Discussionmentioning
confidence: 99%
“…The associations between adipose tissue and female brain health post-menopause may further depend on the individual's lifetime exposure to oestrogens. Studies indicate that levels of cumulative oestrogen exposure, often assessed by reproductive span (age at menarche to age at menopause; (Fu et al, 2022;Gilsanz et al, 2019;Jett et al, 2022)), have lasting effects on brain structure and body composition even after menopause. For example, a longer reproductive span has been linked to larger GM volumes (Schelbaum et al, 2021), lower WM brain age (Subramaniapillai et al, 2022), and lower dementia risk in older-age samples (Fox et al, 2013;Gilsanz et al, 2019;Gong et al, 2022), although contrasting results have linked a longer reproductive span to increased risk of Alzheimer's disease (AD) (Najar et al, 2020;Geerlings et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obesity was associated with an increased dementia risk among women, but a decreased dementia risk among men. Another UK Biobank study found that women with cardiovascular disease had a 20% increased risk for dementia compared to men with cardiovascular disease 13 .…”
Section: Introductionmentioning
confidence: 99%